2023
DOI: 10.3390/ijerph20032118
|View full text |Cite
|
Sign up to set email alerts
|

Informed Consent: Legal Obligation or Cornerstone of the Care Relationship?

Abstract: The topic of informed consent has become increasingly important in recent decades, both in the ethical-deontological field and as a duty of law. The review covered all sentences issued by the 13th section of the Civil Court of Rome during the period January 2016–December 2020. During this period, 156 judgments were found in which a breach of consent was required; in 24 of these, specific liability was proven, and the corresponding compensation liquidated. Moreover, 80% of the cases concerned the lack of inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…It is worth mentioning that these surgical areas were the most litigations specialties due to defective informed consent practices as mentioned by Pallocci et al (2023) among malpractice allegations in Italy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth mentioning that these surgical areas were the most litigations specialties due to defective informed consent practices as mentioned by Pallocci et al (2023) among malpractice allegations in Italy.…”
Section: Discussionmentioning
confidence: 99%
“…Ethically, it ensures that medical care complies with the patient's best interest and supports patient autonomy. Legally, it regulates the physician-patient relationship with subsequent protection of patients from being assaulted, and physicians from being accused of malpractice (Pallocci et al, 2023).…”
Section: Introduction mentioning
confidence: 99%
“…An analysis carried out in Rome, Italy, during the five years between January 2016–December 2020 showed that the Civil Court of Rome considered 1117 malpractice cases [ 24 ]. From January 2018 to February 2019, 280 cases regarding legal liability for malpractice were submitted to trial, representing about 20% of all national disputes [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…The lack of information or the difficulty in understanding it means that the informed consent form ceases to be an effective tool and becomes a mere bureaucratic formality aimed at avoiding any legal liability [ 15 ]. Although it is not always possible to achieve these objectives, especially in patients with serious pathologies in whom treatments without sufficient scientific evidence are used as a last resort [ 16 ].…”
Section: Introductionmentioning
confidence: 99%